2015
DOI: 10.4236/ijcm.2015.611110
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ankle-Brachial Index, Waist-Hip Ratio, Ejection-Fraction, Obesity, Smoking, Alcohol Habits, Diabetes and Hypertension as Independent Predictors of Complexity and Severity of Coronary Artery Disease

Abstract: Background: The present study was conducted to examine the association between various coronary risk factors and clinical parameters, with special emphasis on ankle-brachial index, in predicting the severity and complexity of coronary artery disease. Methods: Patients diagnosed with coronary artery disease at our hospital between September-2012 and December-2014 were examined in this study. Selected patients were screened for cardiovascular risk factors including diabetes, hypertension, smoking, and alcohol ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…In the current study: there was highly significant difference between groups regarding number of diseased vessels. Also Patients of (intermediatehigh SS) group were more likely to have multi vessel disease than patients of (low SS) group (68.8%versus 8.3%) with p value 0.001 This was concordant with studies conducted by Cherku et al [9] & Hindieh et al [23] showed that the individuals with multi-vessel diseases (MVD) are associated with higher burden of angiographic CAD severity Compared with those with non -MVD with P value 0.047.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the current study: there was highly significant difference between groups regarding number of diseased vessels. Also Patients of (intermediatehigh SS) group were more likely to have multi vessel disease than patients of (low SS) group (68.8%versus 8.3%) with p value 0.001 This was concordant with studies conducted by Cherku et al [9] & Hindieh et al [23] showed that the individuals with multi-vessel diseases (MVD) are associated with higher burden of angiographic CAD severity Compared with those with non -MVD with P value 0.047.…”
Section: Discussionsupporting
confidence: 89%
“…Also the study conducted by Cherku et al [9] stated that DM was highly significant between the study population.…”
Section: Discussionmentioning
confidence: 86%
“…[15] Obesity and lower ABPI scores are predictor of complexity and severity of CAD. [27] Study focused on weight loss stated that the association of higher BMI with low ABPI in overweight/obese adults with diabetes. However, intensive weight loss interventions did not significantly change the ABPI.…”
Section: Discussionmentioning
confidence: 99%